Efficient photocatalytic degradation of crystal violet dye and electrochemical performance of modified MWCNTs/Cd-ZnO nanoparticles with quantum chemical calculations - Sanakousar, M.F.; C.C, Vidyasagar.; Jiménez Pérez, Víctor Manuel; Jayanna, B.K.; Mounesh,; Shridhar, A.H.; Prakash, K. (2021)
Several literature studies have defined the doping technique of ZnO with a Cd (transition metal) for photocatalysis applications. Despite this, the properties and the mechanism behind it have never been completely explained. The present work outlines the effect of Cadmium ion doping on structural, optical, electrochemical impedance and photocatalytic properties of ZnO and Cd-ZnO nanoparticles prepared via simple precipitation method. The prepared Cd-ZnO was characterized using advanced techniques such as powder X-ray diffraction, field-emission scanning electron microscope fitted with energy dispersive X-ray diffraction, UV-visible absorbance spectroscopy and electrochemical impedance were performed on modification of glassy carbon electrode (GCE) with multiwalled carbon nanotubes decorated with ZnO and Cd-ZnO. Moreover, Cd-ZnO NPs displayed superior electrochemical performance than undoped ZnO NPs. Experiments revealed that, as compared to ZnO and higher dopant concentration, the photodegradation of crystal violet was enhanced by the use of 0.5 mol% Cd-ZnO catalyst. The implantation of Cd is assisted by faster carrier separation and transfer efficiency. Tauc’s plots illustrate that the incorporation of Cd ion has decreased the optical band-gap of ZnO samples. After Cd doping, the valence and conduction band of ZnO were modified, contributing to the development of O2 ‐ , resulting in a significant improvement in photodegradation. Mulliken atomic charges and molecular properties computed at B3LYP/6-31G level of theory. The HOMO-LUMO band gap of alleged photocatalysts was calculated using density function theory (DFT). Further to support our hypothesis on degradation of the dye using Cd-ZnO was confirmed by the IR and Mass spectral studies. Computational prediction of toxicity of degraded organic molecules was estimated by Toxicity Estimation Software Tool (TEST) by United States Environmental Protection Agency. FTIR and Mass spectroscopy confirm the 100% degradation of CV-dye under UV chamber (6 W) after 30 min at basic medium. The enhanced electrochemical and photocatalytic efficiency of Cd doped ZnO nanoparticles suggest that they have dual activity in energy and water treatment applications